Comparison of GLP-1RAs vs Other Pharmacotherapy for Obesity - Andrew Overholser; Eric Czech; Linda Speer; Joel Wilson; Alex Overholser (Translation)
Background: The Centers for Disease Control and Prevention (CDC) reports that 42% of adults in the United States (US) are obese, and 10% are severely obese. Obesity has many known associated health risks, and successful treatment decreases those risks. Management always includes diet and lifestyle changes and drug therapy can improve weight loss. The current United States Food and Drug Administration (FDA) approved pharmaceutical therapy choices for long-term use include a combination of phentermine-topiramate, combination bupropion-naltrexone, orlistat, glucagon-like peptide-1 receptor agonists (GLP-1RAs), and dual action GLP-1RAs and gastric inhibitory peptide agonists (GIP).